Quantitative plaque characteristics based on 3D high-resolution vessel wall imaging predict long-term recurrence in intracranial atherosclerotic stroke. - Zhao, Ying; Yang, Jiajia; Dai, Yao; Ma, Yuzhu; Song, Ziyang; Hu, Chunhong; Zhang, Yu (Neuroradiology, 2025)
Purpose: To investigate the association between plaque characteristics observed using three-dimensional high-resolution magnetic resonance vessel wall imaging (3D HRMR-VWI) and the recurrence of ipsilateral stroke in patients diagnosed with symptomatic intracranial atherosclerotic stenotic disease. Methods: The patients with intracranial atherosclerotic acute ischemic strokes between January 2018 and December 2023 were enrolled in this study. All patients underwent 3D HRMR-VWI at baseline and were followed up for ≥ 12 months or until stroke recurrence. Baseline imaging characteristics were systematically assessed. Data analysis utilized the Cox proportional hazards model, Kaplan-Meier curves, and receiver operating characteristic (ROC) curves. Time-dependent ROC analysis quantified the dynamic predictive accuracy of plaque characteristics during follow-up. Results: A total of 74 patients were followed for a mean duration of 35.6 months (range: 1–80 months), with 18 experiencing stroke recurrence. Multivariate Cox regression analysis identified age (HR = 1.055; 95% CI: 1.01–1.10, p = 0.018), plaque burden (HR = 1.066; 95% CI: 1.01–1.13, p = 0.031), and plaque enhancement ratio (HR = 3.538; 95% CI: 1.39–9.00, p = 0.008) as independent predictors of stroke recurrence. Time-dependent ROC analysis revealed that the predictive model achieved the AUC of 0.838 for stroke recurrence at 3 years, surpassing its performance at 1 year (AUC = 0.793) and 2 years (AUC = 0.822). Conclusion: Plaque burden and enhancement ratio were independent predictors of recurrent symptomatic intracranial atherosclerotic stroke. Incorporating age with plaque characteristics enhanced long-term stroke recurrence risk prediction.